Hubungan Ketepatan Peresepan Antibiotik dengan Metode Gyssens dengan Perbaikan Klinis Pasien Rawat Inap Pneumonia Komunitas - Cut Fatia Ulfa; Woro Supadmi; Dyah Aryani Perwitasari; Endang Yuniarti (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Community-acquired pneumonia is an acute inﬂammation of the pulmonary parenchyma caused by bacterial infection. . The main therapy for community-acquired pneumonia is the use of antibiotics. Inappropriate antibiotics can lead to bacterial resistance. The study aims to determine Appropriateness of antibiotics prescribing using the method Gyssens with clinical improvement. This study is a retrospective analytic cohort descriptive. Data was collected retrospectively based on medical records of inpatients at one of the hospital in Yogyakarta for the January-December 2019 period based. The accuracy of empiric antibiotic prescription using the Gyssens method. The clinical improvements observed were leukocyte count, temperature, respiratory rate. This study was analyzed using the chi square method. The results showed 41 patients met the inclusion and exclusion criteria, male gender (51.2%), age> 60 years 68.3%, the average length of stay was ﬁve days. Ceftriaksone is a commonly used antibiotic. Evaluation prescribing appropriateness based on the Gyssens method of 52 antibiotic regimens. appropriate antibiotic prescribing (13.5%) and inappropriate (86.5%). The correlation between appropriateness of antibiotics prescribing with clinical improvement leukocytes count, respiratory rate and temperature did not signiﬁcant (p> 0.05). There was no correlation between the accurasy of antibiotics prescribing based on the Gyssens method with clinical improvement.